DOI: 10.17760/d20281159
|View full text |Cite
|
Sign up to set email alerts
|

High school science teachers' receptivity to the next generation science standards : an examination of discipline specific factors

Abstract: The Next Generation Science Standards (NGSS), are the biggest change to American science education since the National Science Education Standards (NSES) were published. While inquiry was central to the NSES, science assessment largely addressed factual knowledge acquisition.The NGSS represent a significant practical change for teachers as they mark a return to the ideals specified in the National Science Education Standards (NSES) and Benchmarks for Science Literacy. The purpose of this explanatory sequential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 102 publications
(192 reference statements)
1
3
0
Order By: Relevance
“…The study revealed the significant relationships between attitudes, behavioral intentions, and perceived behavioral control (i.e., perceived school support, other support, participation in decision-making, and issues of concern). These results are consistent with the previous studies about curriculum change in the education context (Waugh & Godfrey, 1993;Moroz, 1999;Lee, 2000;Lee et al, 2011;Ha et al, 2010;Shapiro, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The study revealed the significant relationships between attitudes, behavioral intentions, and perceived behavioral control (i.e., perceived school support, other support, participation in decision-making, and issues of concern). These results are consistent with the previous studies about curriculum change in the education context (Waugh & Godfrey, 1993;Moroz, 1999;Lee, 2000;Lee et al, 2011;Ha et al, 2010;Shapiro, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The questionnaire used in this study contained 41 items, on a 7-point Likert scale, which were adapted from the validated "Receptivity to Change" instruments of Waugh and Godfrey (1993), Lee (2000), and Shapiro (2018). The questionnaire contained the six variables such as teachers' attitudes, behavioral intentions, perceived school support, perceived other support, perceived participation in decision-making, and issues of concern.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations